THE ANALYSIS OPTIMIZATION ANALYSIS OF BUDGET ABSORPTION OF STATE UNIVERSITY OPERATIONAL ASSISTANCE FUNDS (BOPTN) IN FEB, FISIP, AND FH LAMBUNG MANGKURAT UNIVERSITY - Jupriadi, Jupriadi; Aslamiah, Aslamiah; Suriansyah, Suriansyah (Journal of K6, Education and Management, 2019)
This study aims to describe the optimization model of BOPTN budget absorption on FEB, FISIP and ULM FH 2016 S / D 2018 and identify constraints faced in optimizing the budget absorption. This research is a qualitative research with descriptive methods and quantitative data presentation. The research results of budget absorption in FEB, FISIP, and FH ULM Banjarmasin units from 2016 S / D in 2018 experienced a significant increase in BOPTN fund absorption optimization. This is intended from the percentage numbers in the recapitulation of budget realization in the FEB, FISIP, and ULM Banjarmasin work units which reached 100% in 2017 and 2018. Employee competencies and budget absorption performance have a unidirectional relationship, if employee competencies are higher, the higher also the level of performance of budget absorption. Similarly, the role of information technology is so important in the budget process. Maintenance and repair of hardware and software that are compiled in a comprehensive, clear and periodic manner.